Oncogenic KRAS creates an aspartate metabolism signature in colorectal cancer cells. (27th July 2021) - Doubleday, Peter F.; Fornelli, Luca; Ntai, Ioanna; Kelleher, Neil L.
Abstract : Oncogenic mutations in the KRAS gene are found in 30–50% of colorectal cancers (CRC), and recent findings have demonstrated independent and nonredundant roles for wild‐type and mutant KRAS alleles in governing signaling and metabolism. Here, we quantify proteomic changes manifested by KRAS mutation and KRAS allele loss in isogenic cell lines. We show that the expression of KRAS G13D upregulates aspartate metabolizing proteins including PCK1, PCK2, ASNS, and ASS1. Furthermore, differential expression analyses of transcript‐level data from CRC tumors identified the upregulation of urea cycle enzymes in CRC. We find that expression of ASS1 supports colorectal cancer cell proliferation and promotes tumor formation in vitro . We show that loss of ASS1 can be rescued with high levels of several metabolites. Abstract : Mutations in the KRAS gene, which encodes a small GTPase, are a hallmark feature of 30–50% of colorectal cancers. Recent studies have highlighted the role of metabolic rewiring in colorectal cancer (CRC) and this work sought to explore the impact of KRAS mutation in this context. Using quantitative proteomics, the authors show that cells harboring the G13D KRAS mutant show significant upregulation of enzymes involved in aspartate metabolism, including argininosuccinate synthase (ASS1). These enzymes are also upregulated at the transcript level in KRAS ‐mutant primary CRC. The authors demonstrate that ASS1 is required for colorectal cancer cell growth and supports tumor formation in vitro .